Analyses of software testing problems in Small and Medium Software Enterprises (SME’s) and a proposed framework on exploratory testing / Murugan Thangiah and Shuib Basri - Thangiah, Murugan; Basri, Shuib (2015)
In the field of IT, the software industry recognizes the value of the small and medium software (SME’s) enterprises in contributing valuable products and services to the economy. In SME’s the quality of the software is increasingly become a concerned subject. The suitable use of testing standards was not written for the development organizations having less than 25 employees. Currently, most of the SME’s do not follow any standards and do not adopt any well structured testing methods. In this research paper, the challenges faced by the SME’s towards software testing in order to produce quality products are being addressed. Various testing processes are analysed and discussed in the literature review; to identify which methods are best suitable for the SMEs and to come out with a research question. Further study on the research question will lead to a solution by proposing an acceptable framework of the testing process called Exploratory Testing.